Single newborn screen or routine second screening for primary congenital hypothyroidism - Shapira, Stuart K. (Mol Genet Metab, 2015)
Routine second screening of most newborns at 8–14 days of life for a panel of newborn conditions occurs in 12 U.S. states, while newborns in the other states typically undergo only a single routine newborn screen. The study objective was to evaluate screening consequences for primary congenital hypothyroidism (CH) in one- and two-screen states according to laboratory practices and medical or biochemical characteristics of screen-positive cases. Individual-level medical and biochemical data were retrospectively collected and analyzed for 2,251 primary CH cases in one-screen (CA, WI) and two-screen (AL, DE, MD, OR, TX) states. Aggregate data were collected and analyzed for medical and biochemical characteristics of all screened newborns in the states. Among the states evaluated in this study, the detection rate of primary CH was higher in the one-screen states. In the two-screen states, 11.5% of cases were detected on the second screen. In multivariate analyses, only race/ethnicity was a significant predictor of cases identified on the first versus second screen, which likely reflects a physiologic difference in primary CH presentation. Newborn screening programs must heed the potential for newborns with CH not being detected by a single screen, particularly newborns of certain races/ethnicities. If the two-screen states converted to a single screen using their current algorithms, newborns currently identified on the routine second screen would presumably not be detected, resulting in probable delayed diagnosis and treatment. However, based on the one-screen state experiences, with appropriate modifications in screening method and algorithm, the two-screen states might convert to single screen operation for CH without loss in performance.